Analyzing the Impact of Digital Transformation on the Organization Future A Survey of the Opinions of a Sample of Staff in Private Institutes in the Zakho Independent Administration - Hashim Ali Ahmed; Hoshang Abdulhameed Abdulhadi (Zanco Journal of Human Sciences, 2026)
Research objective: To determine the extent to which digital transformation impacts the future of the organization at private institutes in the Zakho Independent Administration. Research methodology: The research adopted a descriptive and analytical approach because it allows for adaptation to the nature of the data and research conditions. Research population and sample: The research population comprised all functional staff (administrative and teaching) at private institutes in the Zakho Independent Administration, totaling (112). (112) questionnaires were distributed to these individuals and (86) valid questionnaires were retrieved for statistical analysis to form the research sample. Data collection and analysis methods: The questionnaire was used as the primary tool for collecting data for the analytical aspect. Data was analyzed using (SPSS. V.27)using a number of statistical methods, including arithmetic means, standard deviations, frequency percentages, correlation coefficients, and regression. Main research results: Digital transformation and its dimensions have a positive and direct impact on the future of the organization at the researched institutes. Main research recommendations: The management of the researched institutes must engage their staff in the digital transformation process and develop them through technology courses, which will build a better future for the institutes.